The importance of nursing in the post-operatory of mastectomized women with dissection of axillary lymph nodes: integrative review (Research, Society and Development, 2021)
The study aims to recognize the importance of nurses in the postoperative period to assist women in the rehabilitation of mastectomy with dissection of axillary lymph nodes. This is an integrative review, which took place through a survey in the database of the Virtual Health Library, where data from LILACS, SciELO, Bdenf, among others, are available. In view of the analysis of the data collected, applying the inclusion and exclusion criteria, the following categories emerged: Nursing in the recommendations to women with knowledge deficits submitted to mastectomy and Reception to women with body image disorder. It was observed that the care provided by the nursing team to women in the post-mastectomy rehabilitation period, provides great benefits when used together with educational actions, guidance and active listening. In addition, the support network - friends, family and health professionals - is of fundamental importance in accepting self-image and adhering to postoperative recovery.